A Genetic Variant of the ROBO3 Gene is Associated With Adolescent Idiopathic Scoliosis in the Chinese Population. Issue 2 (15th January 2023) - Zhang, Zheng; Zhang, Zhanrong; Shu, Lun; Meng, Yichen; Ma, Jun; Gao, Rui; Zhou, Xuhui
Abstract : Study Design: A case-control association study. Objectives: This study aimed to reveal whether mutations within roundabout receptor 3 ( ROBO3 ) gene were related to adolescent idiopathic scoliosis (AIS) in Chinese Han population and to investigate the functional role of ROBO3 in the pathogenesis and progression of AIS. Summary of Background Data: ROBO3 is essential for the regulation of hindbrain axonal cell migration and midline crossing. Studies have demonstrated that ROBO3 homozygous mutations are associated with horizontal gaze palsy with progressive scoliosis. However, whether and how ROBO3 contributed to the development of scoliosis remains unclear. Materials and Methods: Whole exome sequencing was performed in 135 AIS patients and 267 healthy controls to evaluate the differences of single nucleotide polymorphism variants within ROBO3 . Then the identified variant of ROBO3 was genotyped in another cohort included 1140 AIS patients and 1580 controls. Moreover, paraspinal muscles were collected from 39 AIS patients and 45 lumbar disk herniation patients for the measurement of ROBO3 mRNA expression. The χ 2 test, Fisher exact test or the Student t test were used to compare intergroup data. Pearson correlation was used to determine the association between ROBO3 expression and clinical phenotypes. Results: A significant association was identified between the gene variant (rs74787566) of ROBO3 and the development of AIS through exome sequencing. The genotyping cohort demonstrated a higher frequency of allele A in AIS patients compared to controls (7.89% vs . 4.30%, P <0.001, odds ratio=1.87). In addition, the expression of ROBO3 in paraspinal muscles was inversely correlated with the Cobb angle ( P =0.043, r 2 =0.1059). Conclusion: A significant association was identified between the gene variant (rs74787566) of ROBO3 and the development of AIS. The reduced expression of ROBO3 could result in the progression of curve magnitude in patients with AIS. Further studies are needed to verify the functional role of ROBO3 in the development of AIS. Level of Evidence: Level III.